AB0678 Predictive Value of Capillaroscopy in Early Diagnosis of Systemic Sclerosis in Patients with Positive Anti-Centromere or Anti-Topoisomerase Antibodies. (9th June 2015) - Movasat, A.; Moruno, H.; Turriόn, A.; Bohorquez, C.; Pérez, A.; Cuende, E.; Sanchez, A.; Albarran, F.; Romero, M.L.; Ruiz, L.; Alvarez Mon, M.
Abstract : Background: Systemic Sclerosis (SSc) is a multisystem autoimmune disease characterized by fibrosis of the skin and internal organs and vascular damage. The diagnosis is usually made in the late stages, when irreversible damage has already occurred. Recently, we have established new criteria to detect early cases of the disease. Performing capillaroscopy and its findings are crucial in the diagnosis of early SSc or "prescleroderma" and there may be changes seen in capillaries of patients without skin manifestations. Objectives: To analyze the nailfold capillaroscopy findings in patients with anti-centromere or anti-topoisomerase antibodies and evaluate their usefulness for the diagnosis of SSc. Methods: Of a total of 212 capillaroscopy performed between January 2012 and December 2014, those patients with positive anti-centromere or anti-topoisomerase were selected. In all cases, capillaroscopy was performed in eight fingers, always by the same observer. The following findings were considered pathological or scleroderma pattern: Local or global capillary loss (>20%), Hemorrhages: two or more in at least two fingers and Enlarged capillaries: two or more capillary with double or more caliber in at least two fingers.Statistical analysis was performed with SPSS 19.0 program. Results: The study included 61 patients: 4 (6.6%) males and 57 (93.4%) women, 14 (23%) smokers, 39 (63.9%) non-smokers and 8 (13.1%) quitters. The characteristics of the patients included in the study were as follows: 19 patients (31.1%) were previously diagnosed of SSc (18 limited and one diffuse), of which 4 (21%) patients had concomitant primary biliary cirrhosis Syndrome (PBC), 1 patient with PBC and positive anti-centomere without the presence of Raynaud's phenomenon (RP), one patient diagnosed with Sjögren's syndrome with positive anti-centromere without presence of RP, 22 patients with suspected early SSc and 18 patients with disease-specific autoantibodies in the absence of RP. Digital ulcers were observed in 6 patients (9.8%), all in patients with a previous diagnosis of SSc. Capillaroscopy was normal in 28 patients (45.9%) and pathological in 33 patients (54.1%); we detected limited enlarged capillaries in 26.2%, generalized enlarged capillaries also in 26.2%, giant capillaries in 37.7%, local loss of capillaries in 27.9%, global loss of capillaries in 8.2%, hemorragies in small claims in 29.5% and abundant hemorrhagies in 9.8%. All patients previously diagnosed of SSc had a pathological capillaroscopy except one. However, no changes were observed in patients who had only disease-specific autoantibodies in the absence of RP. While, the 22 patients who were referred for suspected SSc (at least with the presence of RP and autoantibodies) in 15 (68.2%) of these scleroderma pattern was observed with subsequent diagnosis of early SSc or "prescleroderma". Conclusions: Nailfod capillaroscopy is a useful and inexpensive tool for the diagnosis of SSc. The scleroderma pattern is very specific of this disease and we can make an early diagnosis even in patients who only have autoantibodies and RP, without the presence of other severe manifestations. We have also observed that the absence of RP is associated with a normal result on capillaroscopy. Disclosure of Interest: None declared